Análise das propostas de solução e mitigação das inundações em Petrópolis/RJ - Silva, Pedro Henrique de Lima (2024)
The city of Petrópolis has been constantly suffering from rains. The recurrence of this phenomenon is the cause of deaths, trauma and losses for an entire population. This problem is not so current, with reports of floods dating back to 1834. The Imperial city is crossed by the upper course of the Piabanha river and has the Quitandinha river as its best-known and most problematic tributary, where there is the highest rate of land use and occupation and highest average annual rainfall, making the region a scenario prone to tragedies, especially from October to March, where rains occur with greater frequency and intensity. To learn about the history of floods in the municipality and the solution and mitigation proposals that have already been debated and defended, a search was carried out in the digital collection of the National Library of Brazil for newspapers in the state of Rio de Janeiro with terms related to floods and proposals to combat these in the main river basins of Petrópolis. The results of this research were compiled and divided into records of flood occurrences and proposals for solving them. The records found point to the occurrence of floods since before the city was founded, causing damage throughout its history. Several proposals for solving and mitigating floods have been raised, debated and defended since the city was created, however only the construction of the Palatinate River overflow tunnel was carried out. There is no consensus on the solution to flooding in the municipality and some ideas have been debated for more than 170 years. There is no strategic planning to solve floods. The solutions proposed throughout history have positive and negative points. In view of this, this research proposes the creation of the Municipal Flood Control Plan to establish intervention parameters divided into four stages for rains with recurrence times of 2, 5, 10 and 50 years. Starting from non-structural measures and nature-based solutions to complex engineering works such as the creation of detention basins and an overflow tunnel for the Quitandinha River. This research has as its product the creation of a book narrating the history of floods in Petrópolis and providing technical guidelines for the elaboration of this plan and the guidance of structural and non-structural actions to combat the floods that constantly occur in the city.